Purification and Properties of Acetate Kinase from Acholeplasma laidlawii - Kahane, Itzhak (1979)
Acetate kinase (EC 2.7.2.1) was purified from Acholeplasma laidlawii cytoplasm by a combination of ammonium sulfate fractionation, gel filtration, diethylaminoethyl-cellulose chromatography, and affinity chromatography on 8-(6-aminohexylamino)-adenosine 5′-triphosphate conjugated to Sepharose 4B. The enzyme was composed of polypeptide chains of about 50,000 molecular weight as estimated from sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Under nondenaturating conditions, apparent molecular weights between 64,000 and 130,000 were obtained, depending upon mainly the ionic strength of the test solution. The enzyme had a narrow specificity for phosphate acceptor acids, whereas both purine and pyrimidine nucleoside triphosphates were suitable phosphate donors. Na(+) and K(+) inhibited both acetyl phosphate and adenosine 5′-triphosphate synthesis, and the latter was also inhibited by high concentrations of adenosine 5′-diphosphate and acetyl phosphate. This substrate inhibition was partially abolished by 0.5 M NaCl. The enzyme catalyzed the independent adenosine 5′-diphosphate↔adenosine 5′-triphosphate and acetate↔acetyl phosphate exchanges. The rate of the latter was enhanced by the addition of cosubstrate Mg(2+)–adenosine 5′-triphosphate. The high affinity for substrates, except for acetate, indicated that under physiological conditions the direction of the enzymic reaction favors adenosine 5′-triphosphate synthesis. Thus, a mechanism for adenosine 5′-triphosphate generation in mycoplasmas is suggested.